Biologically Synthesized Gold Nanoparticles with Enhanced Antioxidant and Catalytic Properties - Melinda David; Teodor A. Enache; Lucian Barbu-Tudoran; Camelia Bala; Monica Florescu (MDPI AG, 2024)
Increasing levels of reactive oxygen species generate oxidative stress in the human body that can lead to various medical conditions. The use of nanomaterials exhibiting antioxidant properties may prevent these effects. The biological synthesis of metallic nanoparticles using plant extracts with antioxidant properties can offer benefits due to their active compounds. The used extracts contained reducing and stabilizing agents, which were shown to be transferred onto the gold nanoparticles, functionalizing them. Herin, we report a gold nanoparticle synthesis by eco-friendly biological methods (b-AuNPs) using extracts of sea buckthorn, lavender, walnuts, and grapes, obtained through ultrasound-assisted extraction and pressure-enhanced extraction. The obtained b-AuNPs were characterized by UV-Vis and FTIR spectroscopies and visualized using transmission electron microscopy. The catalytic and scavenging effect of the b-AuNPs towards H2O2 (as reactive oxygen species) was evaluated electrochemically, highlighting the protective behavior of b-AuNPs towards lipid peroxidation. All experiments demonstrated the stability and reproducibility of prepared b-AuNPs with enhanced antioxidant and catalytic properties, opening a new perspective for their use in biomedical applications.